Heavy Metal Contamination in Soils of Garbage Area in Van, Turkey - Kiliel, Fevzi (Asian Journal of Chemistry, 2010)
In this study, some heavy metal concentrations in soils of the garbage area in Van, Turkey, by flame atomic absorption spectrometry (FAAS) have been determined. Ni, Co, Cr, Cd and Ca concentrations are the highest; Zn, Cu, Mn and Fe concentrations are higher than control sample concentrations. Metal concentrations in the spring season are higher than in the autumn season except Cd. Wastewater of this garbage area enters into the soil and Puddle Sihke where the water of Puddle Sihke is used as irrigation water and arrives at Lake Van.